2013
DOI: 10.1182/blood-2012-07-443713
|View full text |Cite
|
Sign up to set email alerts
|

Novel interferon-based pre-transplantation conditioning in the treatment of a congenital metabolic disorder

Abstract: Key Points• Type I IFN preconditioning enhances HSC engraftment efficiency.• IFN-based pre-transplant conditioning is applicable to the treatment of Sly syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Given the success of full myeloablative conditioning the results have been attributed to insufficient myeloablation of host cells. To enhance the level of myeloablation without the accompanying undesirable systemic effects, chemo/irradiation-reduced regimens have been combined with myelospecific treatments (Fewkes et al, 2010) or interferon induction (Sato et al, 2013) to reduce host stem cells, and promising results using these strategies have been documented in mice. In the present study we attempted to incorporate similar strategies in an autologous hematopoietic stem cell transplantation (HSCT) setting in the nonhuman primate model using pigtailed macaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the success of full myeloablative conditioning the results have been attributed to insufficient myeloablation of host cells. To enhance the level of myeloablation without the accompanying undesirable systemic effects, chemo/irradiation-reduced regimens have been combined with myelospecific treatments (Fewkes et al, 2010) or interferon induction (Sato et al, 2013) to reduce host stem cells, and promising results using these strategies have been documented in mice. In the present study we attempted to incorporate similar strategies in an autologous hematopoietic stem cell transplantation (HSCT) setting in the nonhuman primate model using pigtailed macaques.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of anti-host HLA MHC class I antibody resulted in transient, partial, and reversible reduction in colony-forming unit-spleen (CFU-S) and colony-forming unit-erythroid (CFU-E) cells in bone marrow (BM) (Sadelain et al, 1990). Further insightful studies have predicted and demonstrated improved donor engraftment with low-dose irradiation, or nonmyeloablative chemotherapy (5-fluorouracil or cyclophosphamide [Cytoxan]) when combined with Kit ligand (KL) (Neta et al, 1993;van Os et al, 1997), granulocyte colony-stimulating factor (G-CSF), or interferon alfa-2a induction (Sato et al, 2013). Inhibition of c-Kit and its binding to stem cell factor (SCF), using monoclonal antibodies (ACK2) and multitargeted tyrosine kinase inhibitors (Sunitinib) alone, has also been demonstrated to improve engraftment in immunodeficient mice but only in combination with low-dose irradiation in immunocompetent mice (Fewkes et al, 2010;Xue et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that IFN-γ may participate in the pathogenesis of IDDM [ 144 ]. A study demonstrated that type I IFN-based pre-BM transplant conditioning was applicable to the treatment of congenital metabolic disorder-Sly syndrome [ 145 ]. IFN-λ1 has been demonstrated to play an important role in regulating metabolic disease.…”
Section: Therapeutic Perspective Of Ifn In Obesity and Insulin Sensit...mentioning
confidence: 99%